QUALIDADE FISIOLÓGICA E SUPERAÇÃO DE DORMÊNCIA DE SEMENTES, AVALIAÇÃO NUTRICIONAL DE MUDAS EM VIVEIRO E CULTIVO in vitro DE Prunus campanulata (Maxim.) - CZELUSNIAK, DANIELA SANSON (2023)
Studies on the physiological quality of seeds, dormancy, nutritional needs, and micropropagation alternatives are important for planning the production of forest seedlings. Thus, the objective of this research was to evaluate methods for overcoming seed dormancy, seed storage potential, effects of mineral and organic fertilization on seedling production and in vitro propagation of Prunus campanulata. To evaluate seed dormancy, an imbibition curve analysis was performed and the three-phase profile was stipulated for three treatments (intact seeds, scarified seeds and seeds without endocarp). For the germination test, seven dormancy-breaking treatments were tested: intact seeds; mechanical scarification; mechanical scarification + imbibition in water at 25 ºC; mechanical scarification + imbibition in water at 80 ºC, removal of the endocarp; removal of the endocarp + imbibition in GA3 (1.5 mg L-1) and removal of the endocarp + imbibition in GA3 (3 mg L-1), evaluating the germination (G, %), germination speed index (IVG) and mean germination time (TMG, days). In order to evaluate the influence of the environment on seed morphometry and quality, seeds from three areas were collected (Irati, Palmeira and Curitiba) and evaluated regarding the length, width and weight of the seeds, in addition to the germination test, evaluating G, IVG and TMG. For storage, the origins of Curitiba and Irati were evaluated. The seeds were processed, disinfested and stored in sealed polyethylene bags in a refrigerator (7 ± 2 ºC); cold chamber (18 ± 2 °C) and at room temperature (25 ± 2 °C) at different storage periods (180, 360 and 540 days) in a completely randomized (DIC) factorial scheme (2 x 3 x 3) (two collection sites x three storage conditions x three storage periods). At the end of each storage period, the moisture content, germination potential and tetrazolium test were evaluated. Also, seedling emergence and biometric characteristics (root collar diameter and shoot length) on substrates of different compositions (pine bark, peat and mixture between both (1:1) were evaluated. After emergence, different types of fertilization were tested: without fertilization; fertilization with controlled release mineral fertilizer (Basacote®, Plus 6M); fertilization with organic fertilizer (poultry manure) and fertilization with different proportions of the mixture of the two types of fertilizers. At 120 and 180 days of age, we evaluated the root collar diameter, plant height, root length, number of leaves, dry mass of shoots and roots, Dickson’s quality index, and macronutrient (N, P, K, Ca, Mg and S) and micronutrients (Fe, Mn, Zn, Cu and B) accumulations in the aerial and root parts of seedlings. Finally, to evaluate an in vitro micropropagation protocol for the species, the seeds were germinated in WPM medium with different concentrations of activated charcoal (0.0, 1.0, 2.0 and 3.0 g L-¹). Then, in the multiplication, rooting and acclimatization stage, three concentrations of sucrose (15, 30 and 45 g L-1) and three types of sealing (plastic film, rigid polypropylene lid and rigid lid with membrane) were evaluated in DIC in a factorial scheme (3 x 3) using sprouts of approximately 1 cm in length, containing two pairs of leaves, taken from seedlings germinated in vitro. The results obtained from the imbibition curve showed that the endocarp restricts the entry of water into the seeds and, consequently, germination. Removal of the endocarp followed by imbibition in GA3 at concentrations of 1.5 and 3.0 mg L-1 were effective in overcoming P. campanulata seed dormancy. We observed that seeds collected from different sources showed morphometric variability and did not influence the germination percentage. The tetrazolium test proved to be effective for evaluating seed viability. Regarding storage, seeds stored in polyethylene packaging in a refrigerator (7±2 °C) is the most suitable for preserving seed viability for up to 360 days. The substrates tested did not influence the emergence of seeds and the biometric variables of seedlings, and can therefore be recommended for the emergence of the species in the nursery. At 120 and 180 days, the seedlings showed significant growth when subjected to no or little supply of mineral fertilizer, while the highest doses of both mineral and organic fertilizer led to a reduction in the development of P. campanulata seedlings. The seedlings were more efficient in absorbing the macronutrients K > N > P > Ca > Mg > S and the micronutrients Fe > Mn > B > Zn > Cu, and the substrate composed of turf + vermiculite presented good conditions to supply the nutritional demands and promote the initial growth of seedlings of the species under nursery conditions. The addition of activated charcoal to the culture medium benefited the initial growth of seedlings of the species. The addition of sucrose in the culture medium, in concentrations ranging from 15 to 30 g L-1, favored in vitro rooting. The use of sealing with a permeable membrane made it possible to obtain more vigorous shoots in vitro, with a higher percentage of rooting and root length, and improved the acclimatization phases with a higher percentage of survival and biometric characteristics of the obtained seedlings. This research contributes to a better understanding of the dormancy characteristics, seed physiological quality, seedling production, and in vitro propagation of P. campanulata.